Organização sindical dos trabalhadores e trabalhadoras rurais do Espírito Santo : o processo de construção da FETAES - Jesus, Charles Travezani de (2011)
This paper seeks, through interviews and documentary analysis traced the history of formation and consolidation of the Federation of Agricultural Workers of the Holy Spirit and thus understand the positions of the organization forward changes that have occurred in Brazil from the 1960s until the late 1990. Assuming that the peasant movements are an expression of capitalist society and in the case of Brazil in a dependent capitalist country, we will, in a first moment of our work we seek to understand the place of Brazil in a globalized capitalist economy and how that development of competitive social order creates contradictions that will lead the rebellions of the field. The second time the work was aimed to understand how the process of maturation of peasant movements particularly with respect to the emergence of the Peasant Leagues linked to Julian Francis and the intervention of the Brazilian Communist Party. At this time we will also seek to understand how the movement promoted by these two organizations will create the basis for the emergence of trade union Movement of Rural Workers (MSTTR). Featuring the work of the PCB that will promote along with the Labor Party a major process of unionization of agricultural workers. The MSTTR at the beginning of the 1960s will reach its zenith with the advent of the Confederation of Agricultural Workers (Contag). At the same time, Brazil was being ruled by a president who somehow approached the popular movements suffer a military coup and the union movement is to be towed thereby inaugurating the phase state of the union scabs MSTTR. The Federation of Agricultural Workers of the Holy Spirit comes in the midst of military rule and even the 1980s will be hegemony of the scabs. In the 1970s a new political group becomes MSTTR articulated in the Holy Spirit, supported by progressive sectors of the Catholic church, this group was called the trade union opposition and then go in the 1980s to compete with the hegemony of the so-called scabs MSTTR . When this group reaches the hegemony of the Brazilian society will be undergoing profound changes that will act in a way to change the positions of union opposition.